EFEKTIVITAS TEKNIK MODELING DALAM MENINGKATKAN KEDISIPLINAN BERIBADAH PELAJAR SMP DI KELURAHAN TURI - Mahatma, Femin; Navion, Febranti Putri (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2021)
This research is motivated by the discipline of praying fardhu prayers for junior high school students who are still low. Modeling technique is one of the techniques in group guidance that applies learning steps by imitating and utilizing group dynamics to be led by researchers. The purpose of this research is to 1) find out whether there is an increase in worship discipline before and after being given the modeling technique, 2) find out whether there is a difference in worship discipline before and after being given the modeling technique. The researcher used a pre-experimental quantitative approach with an intact group comparison design. The population in this research is junior high school students in Turi Village, totaling 20 students, while the sample is 14 junior high school students who have low and very low worship discipline categories, with the division of 7 students for the experimental class and 7 students for the control class. Hypothesis testing using paired sample t-test and n-gain score test. The results obtained are sig. (2 tailed) of 0.000 0.05, and the experimental group's mean value is -69.286, the control group is known to have -2,000 mean value. The results of the n-gain score test in the experimental group obtained an average value of 67%, for the control group the average value was 2%. Based on the results of hypothesis testing, the mean value of the experimental group is higher than the mean value of the control group. So it can be said that the modeling technique is effective in improving the worship discipline of junior high school students in Turi Village.